The Associations between Periodontitis and Respiratory Disease - Moghadam, Somaye Ansari; Shirazaiy, Maseemeh; Risbaf, Sirus (Journal of Nepal Health Research Council, 2017)
Researches have shown positive correlation between periodontitis and respiratory diseases such as chronic obstructive pulmonary disease. We reviewed the literature to assess the relationship between periodontitis and respiratory diseases. This study involved a review of relevant English literature published regarding periodontitis and respiratory diseases during the period of 1994-2015. The analysis of literature related to the topic showed there is association between periodontitis and respiratory diseases such as chronic obstructive pulmonary disease and pneumonia. It was found that periodontitis is associated with respiratory diseases due to poor oral hygiene and low immunity state.